Thermoelectric Generators: Alternative Power Supply for Wearable Electrocardiographic Systems - Dargusch, Matthew; Liu, Wei‐Di; Chen, Zhi‐Gang (Advanced science, 2020)
Research interest in the development of real‐time monitoring of personal health indicators using wearable electrocardiographic systems has intensified in recent years. New advanced thermoelectrics are potentially a key enabling technology that can be used to transform human body heat into power for use in wearable electrographic monitoring devices. This work provides a systematic review of the potential application of thermoelectric generators for use as power sources in wearable electrocardiographic monitoring systems. New strategies on miniaturized rigid thermoelectric modules combined with batteries or supercapacitors can provide adequate power supply for wearable electrocardiographic systems. Flexible thermoelectric generators can also support wearable electrocardiographic systems directly when a heat sink is incorporated into the design in order to enlarge and stabilize the temperature gradient. Recent advances in enhancing the performance of novel fiber/fabric based flexible thermoelectrics has opened up an exciting direction for the development of wearable electrocardiographic systems. This work overviews that both rigid and flexible thermoelectric power generators, with the advantages of eco‐friendliness and maintenance‐free, are suitable for harvesting electricity from the human body to power up wearable electrocardiographic systems. Moreover, advances in flexible thermoelectric materials will further boost the large‐scale application in electrocardiographic systems.